Green and sustainable computing. - Hurson, Ali (Advances in computers. Volume eighty eight, Green and sustainable computing, 2013)
Since its first volume in 1960, Advances in Computers has presented detailed coverage of innovations in computer hardware, software, theory, design, and applications. It has also provided contributors with a medium in which they can explore their subjects in greater depth and breadth than journal articles usually allow. As a result, many articles have become standard references that continue to be of sugnificant, lasting value in this rapidly expanding field. In-depth surveys and tutorials on new computer technologyWell-known authors and researchers in the field<